Diamond Value Management - Knowledge Management And The Measurement Of Value Addition - P. J. Rider (The Southern African Institute of Mining and Metallurgy, 2003)
Diamond Value Management?s objective is to achieve $/ton revenue improvement across De Beers group mines. The respective %improvement contributions are measured against targets set by each of the operations. Degree of target achievement is measured via a maturity model at each operation. DVM comprises seven elements. It spans several value chain facets and various collaborative projects are conducted under its umbrella. New technologies in De Beers are also evaluated from a DVM perspective.